Dimensional analysis of an integrated pump and de-aerator solution in more electric aero engine oil systems. (11th May 2017) - Steimes, J.; Hendrick, P.
ABSTRACT: Aero-engine oil systems need to pump and de-aerate air-oil flows. Engine sub-components performing these tasks are undergoing important changes due to the development of more-electric engines. A new integrated pump and separation system that can be electrically entrained was developed and characterised experimentally to reduce footprint on the engine and increase reliability and performance. This prototype combines the pumping, de-aeration and de-oiling function of the scavenge part of oil systems. Previous works have failed to address in-flight performance of the prototype. To address this need, a dimensional analysis of the Pump and Separation System that allows in-flight performance prediction is proposed in this paper. This model is used to assess different prototype sizes and the influence of a more-electric engine. This analysis illustrates that by switching to an electric entrainment, the footprint of the Pump and Separation system on the engine is reduced by 34%, and de-aeration performances are improved by 55% at maximum take-off and 17% in cruise phase. This study opens the way for a more accurate design of the prototypes based on engine requirements.